Genome-wide identification and evolutionary analysis of neutral/alkaline invertases in Brassica rapa - Eom, Seung Hee; Rim, Yeonggil; Hyun, Tae Kyung (Biotechnology, biotechnological equipment, 2019)
Among the several sucrose-catabolizing enzymes, neutral/alkaline invertases (NINs) play crucial roles in developmental processes as well as environmental stress responses in higher plants. Despite the fact that NINs are essential enzymes for plant life, the NIN family and their evolutionary relationships are poorly understood. Therefore, in this study, we identified 11 NINs in the Brassica rapa (Chinese cabbage; BraNINs) genome, and analyzed the evolutionary mechanisms of BraNIN genes. Evolution analysis suggested that the BraNIN genes were duplicated via a segmental duplication event originating 15.81-45.25 million years ago. Furthermore, two segmental duplicated pairs (BraNIN5/6 and BraNIN7/8) were subject to negative selection. Furthermore, expression analysis of BraNINs using RNA-sequencing data suggested various functions of BraNINs during responses to drought stress. Taken together, our comparative genomic analysis of NIN genes in B. rapa provides information that will assist future studies on sucrose metabolism in sinks and sources of higher plants.